The association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and chronic obstructive pulmonary disease: the mediating role of dietary inflammatory index - Wu, Ruying; Gong, Hongyang (Frontiers in Nutrition, 2024)
Background Numerous studies have indicated a potential correlation between COPD, lipid metabolism, and dietary inflammation. However, the exact mechanisms by which dietary inflammation regulates the pathological processes of COPD related to lipid metabolism remain unclear. NHHR is a novel composite index of atherosclerotic lipid profiles, while the Dietary Inflammatory Index (DII) measures diet-induced inflammation. This study explores the relationship between NHHR and COPD and evaluates whether DII mediates this association. Methods We employed multivariable logistic regression, smooth curve fitting, threshold effect analysis, and subgroup analysis to explore the relationship between NHHR and the incidence of COPD. Additionally, we conducted a mediation analysis to explore the potential relationship between dietary inflammatory index (DII) levels and the relationship between NHHR and COPD. Results This analysis encompassed 13,452 participants, with 2,332 reporting incidents of COPD. Following adjustment for all covariates using multivariable logistic regression, each unit increase in NHHR level and DII level was associated with a 10% (OR = 1.10, 95% CI: 1.05, 1.16) and 8% (OR = 1.08, 95% CI: 1.04, 1.13) increase, respectively, in the incidence rate of COPD. Furthermore, compared to the lowest quartile, the highest quartile of NHHR level and DII level was associated with a 47% (p < 0.001) and 50% (p < 0.001) increase, respectively, in the incidence rate of COPD. Smooth curve fitting and threshold effect analysis revealed a nonlinear relationship between NHHR and the risk of COPD, with a breakpoint at 2.60. Mediation analysis indicated that DII mediated 7.24% of the association between NHHR and COPD (p = 0.004). Conclusion Higher NHHR levels are associated with an increased prevalence of COPD. Moreover, this association is mediated by DII, suggesting that an anti-inflammatory diet may be beneficial.